Kolektif üretim ve bellek bağlamında unutma bahçesine bakış - Aslan, Eda (My University, 2020)
Yazmış olduğum bu eser metni; Unutma Bahçesi Projesi kapsamında üretilmiş olan üç yıllık bir üretim sürecinin çıktılarını okumaya açmaktadır. İstanbul’da bulunan ve günümüzde erişimi mümkün olmayan Alfred Heilbronn Botanik Bahçesi ve kurucu profesörlerini merkezine alan üretimlerin tamamı sanat, botanik, tarih ve kişisel hikayeler ekseninde şekillenmiştir. Üretim sürecinin kendisinin de üretimin bir parçası olduğu bu süreçte transdisipliner bir yaklaşımla bilimsel bir mekânı farklı ölçeklerde kaydetmenin yöntemleri aranmıştır. Tezde yer verilen üretimler, tarih yazımına bir öneri sağladığı düşüncesi ile desteklenmiş ve sergi için üretilmiş olan çalışmaların tamamı ise Alfred Heilbronn Botanik Bahçesi, bahçe mekânında yetişen bitkiler ve bahçeyi kuran profesörlerin hikayeleriyle ilişkilendirilmiştir.

INVESTIGATION OF “THE GARDEN OF (NOT) FORGETTING” IN THE CONTEXT OF COLLECTIVE PRODUCTION AND MEMORYThis text of work that I have written opens the outcomes of a 3-year production process within the scope of the Garden of (Not) Forgetting Project for further reading. All the productions focusing on Alfred Heilbronn Botanical Garden and its founding professors in Istanbul, which is not accessible today, have been shaped in line with art, botany, history and personal stories. In this process, where the production process itself has become a part of production, it has been searched for the methods of recording a scientific place in different scales with an interdisciplinary approach. The productions included in the thesis were supported as they provided suggestions for historiography, and all the productions produced for the exhibition were associated with Alfred Heilbronn Botanical Garden, the plants growing in the garden and the stories of the founding professor.
Keywords: Alfred Heilbronn; Bahçe; Bellek; Botanical; Botanik Garden; Fine arts education; Güzel sanatlar eğitimi; Memory; Öğrenim ve öğretim; Painting; Resim; Study and teaching